Coronary artery endothelial cells and microparticles increase expression of VCAM-1 in myocardial infarction - Radecke, Christopher E.; Warrick, Alexandra E.; Singh, Gagan D.; Rogers, Jason H.; Simon, Scott I.; Armstrong, Ehrin J. (Thrombosis and Haemostasis, 2015)
Coronary artery disease (CAD) is characterised by progressive atherosclerotic plaque leading to flow-limiting stenosis, while myocardial infarction (MI) occurs due to plaque rupture or erosion with abrupt coronary artery occlusion. Multiple inflammatory pathways influence plaque stability, but direct assessment of endothelial inflammation at the site of coronary artery stenosis has largely been limited to pathology samples or animal models of atherosclerosis. We describe a technique for isolating and characterising endothelial cells (ECs) and EC microparticles (EMPs) derived directly from the site of coronary artery plaque during balloon angioplasty and percutaneous coronary intervention. Coronary artery endothelial cells (CAECs) were identified using imaging flow cytometry (IFC), and individual CAEC and EMP expression of the pro-atherogenic adhesion molecule vascular cell adhesion molecule-1 (VCAM-1) was assessed immediately following angioplasty. Patients with MI registered 73 % higher VCAM-1 expression on their CAECs and 79 % higher expression on EMPs compared to patients with stable CAD. In contrast, VCAM-1 expression was absent on ECs in the peripheral circulation from these same subjects. VCAM-1 density was significantly higher on CAECs and EMPs among patients with MI and positively correlated with markers of myocardial infarct size. We conclude that increased VCAM-1 expression on EC and formation of EMP at the site of coronary plaque is positively correlated with the extent of vascular inflammation in patients with myocardial infarction.
Keywords: Acute myocardial infarction; adhesion molecules; VCAM-1; endothelial cells; inflammation; microparticles